2021
DOI: 10.1101/2021.07.15.21260576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet size as a predictor for severity and mortality in COVID-19 patients: a systematic review and meta-analysis

Abstract: Background: Parameters reflecting platelet size can be sensitive indicators that circulating platelets are activated and COVID-19 patients are at increased risk of thrombosis. This systematic review aims to assess the association of mean platelet volume (MPV), platelet distribution width (PDW) and platelet-large cell ratio (P-LCR) with disease severity and mortality in COVID-19 patients. Methods: English and Chinese databases were searched electronically to identify studies reporting data on MPV, PDW or P-LCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This leads to platelet consumption. 25 , 26 At admission, P-selectin expression was significantly increased in severe COVID-19 patients. 27 Rampotas Alexandros and Pavord Sue report that PLTs were aggregated in COVID-19 patients that showed the important role of platelets in thrombotic complications or respiratory failure in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 92%
“…This leads to platelet consumption. 25 , 26 At admission, P-selectin expression was significantly increased in severe COVID-19 patients. 27 Rampotas Alexandros and Pavord Sue report that PLTs were aggregated in COVID-19 patients that showed the important role of platelets in thrombotic complications or respiratory failure in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 92%
“…The authors of [ 80 ] showed that COVID-19 positive cases with high P-LCR (95% CI, 1.40–6.41; p = 0.0046) were significantly associated with worse survivability. The authors of [ 81 ] proposed that P-LCR is the most important biomarker for evaluating platelet activity and could identify COVID-19 individuals with an increased risk of thrombotic events. In another study [ 82 ], the authors proposed the use of a cohort study, in which the values of the P-LCR parameter were significantly higher in COVID-19 individuals than in non-COVID-19 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Because platelet is a key regulator of thrombosis and inflammation, both present in severe COVID-19 patients, it is a good candidate for risk factor (Barrett et al, 2021). However, it is suggested that platelet/large-cell-cell ratio (PLCR) is a better marker than MPV and PDW (Daniels et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Because platelet is a key regulator of thrombosis and inflammation, both present in severe COVID-19 patients, it is a good candidate for risk factor (Barrett et al, 2021; Rohlfing et al, 2021; Delshad et al, 2021). However, it is suggested that platelet/large-cell-cell ratio (PLCR) (Daniels et al, 2021) is a better marker than MPV and PDW, and platelet-to-lymphocyte ratio (PLR) (Asan et al, 2021) is a better marker than platelet count. However, see counter conclusions in (Aydinyilmaz et al, 2021; Lippi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%